Designing the European registry on minimally invasive pancreatic surgery: a pan-European survey - Heijde, Nicky van de; Vissers, Frederique L.; Boggi, Ugo; Dokmak, Safi; Edwin, Bjørn; Hackert, Thilo; Khatkov, Igor E.; Keck, Tobias; Besselink, Marc G.; Abu Hilal, Mohammed (HPB, 2021)
Background - The recent Miami international evidence-based guidelines on minimally invasive pancreatic surgery (MIPS) advise all centers that perform MIPS to participate in multicenter registries to safeguard optimal outcomes and patient safety. During the design phase of a pan-European registry on MIPS, the European consortium of Minimally Invasive Pancreatic Surgery (E-MIPS) sought input from European HPB surgeons. - Methods - An anonymous online questionnaire with 23 questions on MIPS practice was sent to all member centers of the European-African Hepato-Pancreato-Biliary Association (E-AHPBA) and E-MIPS. - Results - Completed questionnaires were obtained from 98 centers in 23 countries, of which 75 (76.5%) were academic centers. Centers had a median annual pancreatoduodenectomy volume of 45. The most-performed MIPS procedure was laparoscopic distal pancreatectomy (93.9% of centers). Minimally invasive pancreatoduodenectomy was performed in 49% of all centers. Some 25 centers already participated in an ongoing national registry, and were willing to share their data with the European registry on MIPS. The most mentioned (45.4%) maximum time for processing one patient's data into the registry was 10-15 min. - Conclusion - This European survey showed considerable support for the European registry on MIPS.
Gesehen am 11.07.2021